Chapter Experience, sensorial skills and personality qualifying a wine consumer as an expert - Fabbris, Luigi (Proceedings e report, 2021)
This paper analyses the characteristics of wine consumers that may qualify them as wine experts. The wine evaluation expertise of consumers, as measured by various degrees of self-perceived ability, is hypothesised to causally depend on cognitive and non-cognitive characteristics of wine experience, on sensorial skills relevant for wine assessment and on wine consumption-related personality aspects. Our work consisted in measuring and analysing the relationships between the self-assessment of the ability to wine assessment given by a convenience sample of consumers and the qualification of their consumption experience and training (ranging from "simple" consumer to producer/seller to professional sommeliers), their sensorial (olfactory, flavour) skills and enogastronomic culture. Wine culture is defined as the capacity to harmonise wine and food and conceive wine as a nutritional, social and health-related means. The analysed data refer to a tasting experiment held as a social activity during a scientific meeting in Pescara, Italy, in 2018. The sample of wine assessors who filled in the evaluation questionnaire included both meeting participants and people belonging to AIS-Abruzzo, the regional association of chartered sommeliers. The data collected at wine tasters showed that there were strong relationships between the self-evaluation as wine expert and the consumption experience, the assessment skills, and the wine consumption "culture". The relationships differed according to age, activity and length of wine consumption experience of the assessors.